The hepatotoxicity of Ageratum conyzoides leaf in experimental rats - Sani, Yulvian; Bustami, saumtira; Grindra, Aisjah (Indonesian Animal Sciences Society, 1998)
Five extracts were obtained from Ageratum conyzoides leaf extracted in methanol-water (4 :1). They were neutral extract (in ethyl acetate), moderately polar extract (in chloroform); basic extract (in chloroform-methanol), polar extract (in methanol), and filtrate. Three extracts were tested biologically and the moderately polar extract was found to be most toxic for female Wistar rats . While the toxicity of neutral extract was mild and other extracts were non-toxic. Therefore, the moderately polar extract was investigated for the hepatoxicity effects in the present study. Intragastric dosing of this extract in rats has caused mortality with clinical signs of weakness, low activity and death. Pathological examination showed mottling on the capsular surface of liver. Microscopically showed anisokaryosis, megalocytosis, bile duct cells proliferation and necrosis . Multiple dosing of this extract may lead to liver and lung injury showing anisokaryosis, megalocytosis, bile duct cells proliferation, centrolobular necrosis, vacuolisation, mitotic figures and mononuclear cells infiltration in the liver and epithelialisation of alveolar walls, thickening of alveolar walls and oedema in the lungs. Liver regeneration occurred 7 days after the last dosing showing mitotic figures and return to the normal structure of liver. The average body weight gain reduced during the first 3 weeks of intoxication from 127.6 g. on predosing to 120,4 g. on week-3 followed by an increased on body weight until the last experiment to 130.8 g. when dosing of extract was terminated . There was an increased of alanine amino transferase ( ALAT) during the first 2 days after dosing from 14.6 IU/1 to 23 .0 IU/1 and reduced at the following days to 7.5 IU/1 at day-5 after dosing . Dosing with retrorsin has caused an increased in ALAT consistently during the first 5 days to 8.7 IU/1 . The activity of aspartate amino transferase (ASAT) reduced during the first 3 days after dosing with the extract from 29 .2 IU/1 to 15 .1 IU/I and from 15 .9 IU/1 to 8.9 IU/1 with retrorsin, but both enzymes appeared higher than control rats . The analysis of toxic Â compound in A. conyzoides leaf showed that the Rf value was similar to retrrorsin showing the leaf containing pyrrolizidine alkaloid compounds. Â Keywords: Ageratum conyzoides, retrorsine, pathology, regeneration, liver, lungs